Semantic Typology Pandemic Vocabulary: Covid Neologisms in English, French and German - N. A. Voskresenskaya (Научный диалог, 2022)
Neologisms that appeared under the influence of the pandemic of a new coronavirus infection Covid-19 are considered, based on the material of English, French and German languages. The basis of the study is formed by neologisms collected by continuous sampling from available lexicographic sources and foreign language Internet resources. The relevance of this work is confirmed by the rapid growth of neologisms in all the languages under consideration. The novelty of the study lies in a comparative approach to the analysis of nomination processes and in determining the dominant areas of semantic attraction in these linguistic cultures. The elements that have shown the greatest productivity and stable functioning are singled out. The author’s classification of covid neologisms is proposed. The question is raised about the susceptibility of these languages to new realities, their productivity in the process of responding to changes in various spheres of society. It is concluded that the number of English neologisms prevails over the corresponding units in French and German. It is confirmed that the structure of the lexico-semantic groups identified during the analysis is heterogeneous and in some cases has a lacunar character. It is suggested that the reason for this may be both the specificity of the word formation of languages, and the peculiarities of the mentality inherent in a particular linguocultural community.